Activities of the Council of Europe towards harmful actions of new religious movements - Matković Aleksandar (Strani pravni život, 2018)
This paper is dedicated to the analysis of the Council of Europe's activities concerning harmful actions of new religious movements. Within the first part of the paper, the author analysed Council of Europe's recommendations directed towards new religious movements. Within the second part, the causes for such Coucil's activism were examined. The third part is focused on establishing the relationship between the activities of the Council of Europe and national anti-cult strategies. Inside the final part, noticed tendencies and regularities were highlighted, together with the general summarization of the achieved insights. Among other things, it was concluded that the Council took a very cautious, liberal and tolerant attitude in relation to the matter of new religious movements. By recommending Member States exclusively to study these issues and educate the population, the Council clearly suggested the avoidance of legislative and other invasive anti-cult measures. Hence, the potential impact of the Council's recommendations can be sought exclusively within those countries that hold similar, liberal and non-invasive approach. By contrast, it is not justifiable to link such Council's influence with the policies of those countries that, contrary to recommendations 1178 and 1412, have opted for more radical (legislative and other) steps. On the other hand, it seems reasonable to assume that, on the contrary, countries with anti-cult legislation and other invasive anti-cult measures could easily influence the radicalization of the position of the Council of Europe, which can be noticed within the latest, yet not officially adopted, documents of the Council: Document 12595 and Report 13441.